Influência da rota alcoólica no processo de organofilização de argilas bentoniticas para uso em fluidos de perfuração não aquosos - Dantas, Suylan Lourdes de Araújo (2013)
Bentonite clays may be defined as a clay consisting predominantly of the smectite group clay minerals, particularly montmorillonite. There is naturally organophilic bentonite clays, these can be modified by specific treatments with surfactants (ionic or nonionic), passing to its hydrophobic nature hidofílica. Organophilic clays are widely used in drilling fluids non-aqueous, these fluids are mixtures of different components used in a well bore. One of the basic characteristics of drilling fluids is to minimize physical and chemical changes of the formations to be drilled. Recent studies have demonstrated the influence of clay, and presence of a dispersant surfactant rheology of the fluids. In this study we verified the influence of clay and surfactant in the production of organoclays using a route alcoholic and was therefore analyzed the rheology of non-aqueous fluids. Therefore, we performed the characterization of samples of clays; through thermogravimetric analysis, X-ray Diffraction, Differential Thermal Analysis and Particle Size Analysis for the organoclays were characterized by XRD and X-ray fluorescence were eventually produced in non-aqueous fluids according to Petrobras to perform normalization of rheological tests. The results indicated that the influence of the ratio clay / surfactant and the route alcoholic on the rheology of non-aqueous drilling fluids.